Unilateral or bilateral drainage for patients with bilateral chronic subdural hematoma: a systematic review and retrospective cohort study - Foppen, Merijn; Yah, K.; Slot, K. M.; van Schie, P.; Verbaan, D.; Vandertop, W. P. (Neurosurgical review, 2025)
Bilateral chronic subdural hematoma (cSDH) can be treated with unilateral or bilateral drainage. Unilateral drainage reduces surgery-related risks but could entail growth of the contralateral, non-operated hematoma. This study aims to (1) determine the incidence of additional contralateral surgery, (2) find factors associated with its occurrence, and (3) evaluate outcomes of uni- and bilateral drainage in bilateral cSDH patients. A systematic review (SR) conducted according to the PRISMA guidelines, pooled incidences of additional contralateral surgery with 95% confidence intervals (CI). Meta-analyses explored factors associated with contralateral surgery. Subsequently, a single-center, retrospective cohort study of bilateral cSDH patients treated with burr hole craniostomy (2010–2022) was performed. The primary outcome was occurrence of additional, contralateral surgery after unilateral drainage. Additionally, surgical complications, 30-day mortality, and reoperation rates (ipsilateral recurrence and additional contralateral surgery) were compared for unilateral and bilateral approaches in all patients and in two subgroups: cases with clinical equipoise regarding surgical approach and a propensity score-matched cohort. The pooled incidence of additional contralateral surgery in 697 patients (SR: 630, cohort: 67) receiving unilateral surgery was 14% (95% CI: 9–19%). Smaller ipsilateral hematoma (mean difference (MD): 12.2 ml, 95% CI: 7.18–17.23) and larger contralateral hematoma (MD: -25.4 ml, 95% CI: -43.95/-6.85) were independently associated with contralateral treatment (meta-analysis SR). Among 178 patients of the retrospective cohort, bilateral drainage had higher complication rates (9.9% vs. 1.5%, p = 0.032). In 93 patients with clinical equipoise and in 56 propensity score-matched patients, surgical approach did not affect reoperation, complications, or 30-day mortality rate. In patients with bilateral cSDH, additional contralateral treatment is required in 14% of all patients. Bilateral surgery carried higher complication risks in our cohort, but in the two subgroups, unilateral or bilateral approaches yielded similar outcomes. Prospective studies are required to further define in which patients unilateral surgery may suffice.